As Praças Centrais de Presidente Prudente-SP: avaliação do caráter como subsídio para intervenções projetuais - Bispo, Thaís Mitie Shiguematsu [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
During the process of development and urban sprawl in the city of Presidente Prudente (SP), some factors as the emergence of new centralities, the change in lifestyles and the expansion of equipments and urban infrastructure contributed to the dismantling and little appropriation of the central open space system. In this sense, the work is about the loss of continuity between the central squares of the city - Monsenhor Sarrion Square, July 9 Square, Bandeira Square and Nossa Senhora Aparecida Square - using different methodologies for character evaluation of each square, identifying the inviting and unattractive aspects of their spaces. The relations between these squares and its surroundings are characterized by analyzing interesting visual played on sketches, to complement character evaluation. Among these studies, it is also analyzed two spatial structures related to the squares – Calçadão and Quintino Bocaiuva Street - which have important architectural referring to the city's history and contribute to the central open space system configuration. General considerations obtained through diagnosis provided subsidies for the projectual proposed intervention, which aims to provide appreciation of the character of these public spaces and their articulation, promoting their use and constituting, thus, an important urban-environment set

Durante o processo de desenvolvimento e expansão urbana do município de Presidente Prudente (SP), alguns fatores como o surgimento de novas centralidades, a mudança nos modos de vida e a ampliação dos equipamentos e infra-estruturas urbanas contribuíram para a desarticulação e pouca apropriação do sistema de espaços livres centrais da cidade. Nesse sentido, o trabalho aborda a perda da continuidade entre as praças centrais da cidade – Praça Monsenhor Sarrion, Praça 9 de Julho, Praça da Bandeira e Praça Nossa Senhora Aparecida – utilizando diferentes metodologias para avaliação do caráter de cada umas das quatro praças, identificando aspectos convidativos ou não atrativos de seus espaços. As relações estabelecidas entre essas praças e seu entorno são caracterizadas através da análise de visuais interessantes reproduzidos em croquis, de forma a complementar a avaliação do caráter. Aliado a esses estudos, são analisados também duas estruturas espaciais vinculadas às praças – Calçadão e Rua Quintino Bocaiúva – que apresentam importantes conjuntos arquitetônicos que remetem à história da cidade e que contribuem para a configuração do sistema de espaços livres centrais. As considerações gerais obtidas através desse diagnóstico forneceram subsídios para a intervenção projetual proposta, que visa proporcionar a valorização do caráter de cada um desses espaços públicos e a articulação dos mesmos, promovendo sua utilização e constituindo, assim, um importante conjunto urbano-ambiental
Keywords: Arquitetura; Planejamento urbano; Projeto arquitetonico; Paisagens e jardins; Presidente Prudente (SP) - Praças